The Influence of Supply Chain Digitalization on Halal Supply Chain Implementation in the Halal Industry - Dwita, Febrisi; Novialumi, Anita; Sumardiono; Elliyana, Ela; Santoso, Budi; Zefanya Purba, Hezkiel (Jurnal Minds: Manajemen Ide dan Inspirasi, 2026)
This study examines how digital innovation in supply chains enhances halal supply chain effectiveness in Indonesia, with implementation success as a mediating mechanism. It contributes theoretically by advancing a socio-technical model that positions digitalization as an enabling condition contingent on organizational and regulatory alignment rather than a direct driver. Using PLS-SEM on survey data from 170 halal-certified food and beverage producers, the findings show that digital technologies significantly improve supply chain success but do not directly translate into implementation. Instead, effective halal practices fully mediate this relationship. The results highlight that technological adoption requires institutional support and managerial commitment. Practically, the study informs policymakers and industry actors to design integrated digital–halal strategies. However, its cross-sectional design and regional focus limit generalizability, suggesting future longitudinal and multi-context studies to capture dynamic transformation patterns.